KONSTRUKSI PERLINDUNGAN HUKUM BAGI PENGADU/PELAPOR KERUGIAN KONSUMEN DARI TUNTUTAN PENCEMARAN NAMA BAIK OLEH PELAKU USAHA/PRODUSEN - Ahmad Zuhairi (Fakultas Hukum Universitas Mataram, 2015)
Now, many consumer who report bed business practices that lost consumer are sued back by businessman. These we can see in the case Dewi Prita Mulyasari, Fery Kuntoro, Fifi Tanang and so on. The accident made a traumatic to consumer who report. It is the problem in consumer protection in Indonesia. That why, this writing try to study implication of law because there is no macanism of law protection to reporter consumer and how to make a rule which give guaranty protection of law to reporter consumer. Purpose of this research is to give a solution in dilemma revenge action from businessman and to encourage honest and responsible business practice atmosfer. This research is normative research with statute approach, conceptual approach and comapartive approach. Implication of nothing rule in national act concerning to protection of law for reporter consumer is businessman can sue consumer with aspersion, inconsistent protection of law for consumer and created much cosumer crime. Thus, construction of law which give protection of law for reporte consumer from aspersion is nomativly there is rule which give imunity for reporter lost consumer from aspersion until there is judgment decision. In application, there is rule which give a policemen reject sue aspersion before judgment decision. Key word; Protection of law, reporter consumer, aspersion